843. Increased Carbapenemase Testing Following Implementation of VA Guidelines for Carbapenem-Resistant Enterobacteriaceae (CRE). (31st December 2020) - Fitzpatrick, Margaret A; Suda, Katie J; Ramanathan, Swetha; Wilson, Geneva M; Jones, Makoto M; Perencevich, Eli N; Rubin, Michael; Klutts, James S; Pfeiffer, Christopher D; Evans, Martin; Evans, Charlesnika T
Abstract: Background: Carbapenem-resistant Enterobacteriaceae (CRE) are a substantial burden, with recent data showing no change in hospital CRE between 2012-2017. All carbapenemases produced by CRE have been identified in the U.S., however trends in testing and detection over time have not been well described. Trends in carbapenemase testing in the VA, 2013-2018 Methods: A retrospective cohort study of Veterans hospitalized between 2013-2018 with CRE cultures defined by either 2015 or 2017 VA guidelines. In general, this was Escherichia coli, Klebsiella pneumoniae/oxytoca, or Enterobacter spp. non-susceptible to imipenem, meropenem, and/or doripenem, and to 3 rd generation cephalosporins for 2015 definition. Testing for Klebsiella pneumoniae carbapenemase (KPC), New Dehli metallo-β-lactamase (NDM), Verona integron-encoded metallo-β-lactamase (VIM), Imipenemase (IMP), and Oxacillinase-48-like (OXA-48) was summarized with descriptive statistics. Facility characteristics assessed included region, complexity, and rurality. Results: Out of 5, 778 CRE cultures, 1, 900 (32.9%) were tested for carbapenemases and 1, 612 (84.8%) of these had carbapenemases detected. Among CP-CRE cultures, 1, 042 (64.6%) had testing for ≥1 genetic mechanism; all tests included KPC. Testing for NDM (n=585, 56.1%), VIM (n=102, 9.8%), IMP (n=102, 9.8%), and OXA-48 (n=507, 48.7%) was less frequent. KPC was detected in 915/1, 042 cultures (87.8%), while NDM (n=7/585, 1.2%) was rarely detected. There were no cases of VIM, IMP, or OXA-48. Carbapenemase testing increased significantly over the study period; KPC, NDM, and OXA-48 were the predominant mechanisms tested (Figure 1). The South (38.6%) and Northeast (37.2%) had the highest proportion of CRE with carbapenemase testing. High complexity (vs low) and urban (vs rural) facilities were significantly associated with carbapenemase testing (p< 0.001). Conclusion: Following publication of initial CRE guidelines in 2015, carbapenemase testing and detection increased in the VA, although tests for non-KPC carbapenemases were less frequent. Surveillance of non-KPC carbapenemases is important due to global dissemination and enhanced antibiotic resistance. Efforts should support carbapenemase testing in low complexity, rural facilities in the Midwest and West. Disclosures: All Authors : No reported disclosures